Adsorption of thiotepa anticancer by the assistance of aluminum nitride nanocage scaffolds: a computational perspective on drug delivery applications - Céspedes Panduro, Bernardo (2023)
This work was carried out by the importance of providing insights into the nano-based drug delivery of anticancers. To this aim, a representative model of aluminum nitride (AN) nanocage scaffold and two of its boron and gallium doped forms (BAN and GAN) were investigated towards the adsorption of thiotepa (Tep) anticancer. Density functional theory (DFT) calculations were performed to evaluate the stabilized structures and their corresponding electronic features. The results indicated the contribution of N-head and S-head of Tep to interactions with each scaffold resulting six complexes; NTep@AN and STep@AN, NTep@BAN and STep@BAN, NTep@GAN and STep@GAN. In each complex model, the characteristic features were obtained based on the interactions details and frontier molecular orbitals related features. In this regard, the investigated scaffolds were found suitable for adsorbing the Tep substance with different strengths and frontier molecular orbitals levels yielding the possibility of assigning specified recovery time and conductance. As a consequence, the models of investigated scaffolds were found suitable to work as possible carriers of Tep anticancer for approaching the nano-based drug delivery purposes.